Time of out-of-hospital cardiac arrest is not associated with outcome in a metropolitan area: A multicenter cohort study. (September 2019) - Schriefl, C.; Mayr, F.B.; Poppe, M.; Zajicek, A.; Nürnberger, A.; Clodi, C.; Herkner, H.; Sulzgruber, P.; Lobmeyr, E.; Schober, A.; Holzer, M.; Sterz, F.; et al.
Abstract: Aim: Whether time of day influences survival after out-of-hospital cardiac arrest (OHCA) remains controversial. We compared outcomes after OHCA between day and night and explored whether characteristics of pre-hospital advanced life support (ALS)-quality varied by time of day. Methods: We conducted a prospective cohort study of individuals that suffered a non-traumatic OHCA in the city of Vienna between August 2013 and August 2015 and who received resuscitative efforts by EMS. We compared clinical outcomes between day and night, defined as 7:00 pm–7:00 am based on EMS shift time including rates of sustained return of spontaneous circulation (ROSC), 30-day survival and favourable neurologic outcome (cerebral performance category 1 or 2). ALS quality measures included time to first medical contact, time to first shock, total dose of epinephrine, and multiple ALS performance measures. Results: We included 1811 patients (37% female) with a mean age of 67 ± 16 years in our analyses. Rates of ROSC and 30-day survival with favourable neurological outcome did not differ between day or night (30% vs 28%, p  =  0.33; 12% vs. 11%, p  =  0.51, respectively). These results remained unchanged after multivariate adjustment for ROSC (RR, 1.1; 95% CI, 1.0–1.3, p  = 0.19) and 30-day survival with favourable neurological outcome (RR, 1.2; 95% CI, 1.0–1.5, p  =  0.10). The quality of ALS did not differ between day and night. Conclusions: In contrast to previous studies, there was no significant difference in sustained ROSC rates and 30-day survival with favourable neurological outcome after OHCA between day and night in the city of Vienna. This is likely due to nearly identical high bystander CPR rates and identical ALS performance provided by EMS personnel irrespective of time of the day.